Psychological Well- Being of Healthcare Workers During The COVID-19 Pandemic - Novi Elisadevi; Taufik Kasturi; Setia Asyanti; Teraika Sri Sulastri (CV. Publikasi Indonesia, 2025)
The purpose of this study was to determine the description of the psychological well-being of health workers during the co-19 pandemic, and to find out the factors that can influence it. The informants in this study totaled 6 people. Informants were selected based on the 42-item Ryff psychological well-being scale score that had previously been distributed in advance, and could reach 96 health worker respondents. Of the 96 respondents, 6 subjects were selected based on their level of psychological well-being, namely 3 subjects with high psychological well-being, and 3 subjects with low psychological well-being. The research was conducted using a qualitative method with a phenomenological approach. Interviews were conducted using an interview guide prepared by the researcher. Data analysis was conducted using interpretative phenomenological analysis. From the results of the analysis, it was found that the psychological well-being of health workers during the Covid-19 pandemic can be influenced by the social support received, the way the subject overcomes the problems faced, and the gratitude he has for his life.